Inactivity and fatty liver disease - Marek Rác; Ľubomír Skladaný; Adam Szulc; Zuzana Mesárošová; Mária Szántová (Kazimierz Wielki University, 2016)
Physical activity represents a key element in the prevention and management of many chronic diseases. On other hand physical inactivity is a primary cause of obesity, metabolic syndrome and nonalcoholic liver disease. A higher body weight is associated with an increased incidence of a number of conditions, including diabetes mellitus, cardiovascular disease and nonalcoholic fatty liver disease. Obesity is associated with a increased risk of all-cause mortality. Hepatic consequence of sedentary lifestyle is nonalcoholic fatty liver disease (NAFLD), which is now in Western countries the most common cause of chronic liver disease. NAFLD primary affects hepatic structure and function. NAFLD cause morbidity and mortality from liver cirrhosis, liver failure and hepatocellular carcinoma. The majority of deaths among NAFLD patients are attributable to cardiovascular disease (CVD) and cancer. NAFLD is strongly associated with the clinical features of insulin resistance and is the hepatic component of metabolic syndrome.